2022
DOI: 10.3390/plants11131658
|View full text |Cite
|
Sign up to set email alerts
|

Brevilin A Isolated from Centipeda minima Induces Apoptosis in Human Gastric Cancer Cells via an Extrinsic Apoptotic Signaling Pathway

Abstract: Brevilin A, which has anticancer activities against a range of cancers, is an abundant constituent of the medicinal herb Centipeda minima (L.) A. Braun & Asch, which has also been reported to have anticancer activity against breast cancer cells. However, the anticancer activities of C. minima and brevilin A against human gastric cancer have yet to be reported. In this study, we aimed to evaluate the cytotoxicity and molecular basis underlying the anticancer activities of extracts of C. minima (CMX) and bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Brevilin A (BA), a natural sesquiterpene lactone, is purified from Centipeda minima herb, a Traditional Chinese Medicine (TCM) initially used to relieve stuffy nose, asthma, and cough [ 3 ]. Recent studies have revealed the great efficacy of BA on antitumor activities, particularly those of the breast cancer [ 3 , 4 ], gastric cancer [ 5 ], colon carcinoma [ 6 ], lung cancer [ 7 , 8 ], glioblastoma [ 9 ], melanoma [ 10 ], multiple myeloma [ 11 ], and nasopharyngeal carcinoma [ 12 ]. Specifically, BA inhibits proliferation, migration, and invasion, in part, through suppressing signaling pathways, including JAK2/STAT3 and PI3K/AKT/mTOR [ 3 , 4 , 6 , 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brevilin A (BA), a natural sesquiterpene lactone, is purified from Centipeda minima herb, a Traditional Chinese Medicine (TCM) initially used to relieve stuffy nose, asthma, and cough [ 3 ]. Recent studies have revealed the great efficacy of BA on antitumor activities, particularly those of the breast cancer [ 3 , 4 ], gastric cancer [ 5 ], colon carcinoma [ 6 ], lung cancer [ 7 , 8 ], glioblastoma [ 9 ], melanoma [ 10 ], multiple myeloma [ 11 ], and nasopharyngeal carcinoma [ 12 ]. Specifically, BA inhibits proliferation, migration, and invasion, in part, through suppressing signaling pathways, including JAK2/STAT3 and PI3K/AKT/mTOR [ 3 , 4 , 6 , 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the in-vivo study indicated the growth-inhibitory activity of Brevilin A by triggering apoptosis and autophagy in tumor tissues. Lee et al (2022) studied the effects of brevilin A on human gastric cancer (AGS) cells. They observed that CMX and brevilin A triggered apoptotic cell death AGS cells by increasing the activated forms of caspase 8 and caspase 3, reducing Bcl-2, and inducing the expression of Bax.…”
Section: Sesquiterpene Lactones With Pro-apoptotic Activities In Cancermentioning
confidence: 99%
“…Yan and coworkers found that costunolide triggered intrinsic mitochondria‐dependent apoptosis through elevating puma and Bax expressions and down‐regulating Bcl‐2 in BGC‐823 cells (Yan, Xu, et al, 2019b). Similarly, brevilin A, an active constituent obtained in Centipeda minima (L.), showed to induce mitochondria‐dependent apoptosis via negatively regulation of Bcl‐2 in AGS cells (Lee et al, 2022). Moreover, Wang and colleagues recently reported that hydroxysafflor yellow B, a bioactive ingredient from the petals of the safflower, caused mitochondria‐dependent apoptosis by promoting Bax expression and down‐regulating Bcl‐2 (Wang, Wang, et al, 2022a).…”
Section: Compounds Prevent Gc Via Regulated Cell Deathmentioning
confidence: 99%